Дослідження навчання роботів на основі досвіду - Пара, І. І. (ХНУРЕ, 2024)
This article provides a review of the literature on reinforcement learning from demonstrations (RLfD), a subfield of machine learning that allows robots to learn from demonstrations by humans or other robots. The goal is to develop a comprehensive understanding of RLfD methods and the irapplications in robotics.
Keywords: навчання роботів; RLfD; машинне навчання